1995
DOI: 10.1002/bjs.1800821225
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant consumption during exercise in intermittent claudication

Abstract: Twenty male claudicant patients and nine age-matched controls were exercised on a treadmill. Blood and urine samples were taken before and after exercise. Total antioxidant concentration was measured using an enhanced chemiluminescent assay and microalbuminuria determined by radioimmunoassay. Claudicants had increased microalbuminuria after exercise. Mean (s.e.m.) antioxidant concentrations were similar for patients and controls at rest: 479(28) and 438(23) mumol/l respectively. Claudicants showed a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 18 publications
0
21
0
1
Order By: Relevance
“…Oxygen-derived free radicals are involved in various diseases affecting the extremities [1][2][3][4][5]. In free radicalrelated processes, lipid peroxidation occurs followed by cellular damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxygen-derived free radicals are involved in various diseases affecting the extremities [1][2][3][4][5]. In free radicalrelated processes, lipid peroxidation occurs followed by cellular damage.…”
Section: Discussionmentioning
confidence: 99%
“…thritis [1], diabetic neuropathy [2], compartment syn drome [3], interm ittent claudication [4], and athero sclerosis [5]. However, next to free radicals, other in flammatory mediators [6,7] and alterations in cellular energy metabolism [8] contribute to the tissue damage in these processes.…”
mentioning
confidence: 99%
“…The beneficial effect of antioxidant intervention in claudicants has been suggested previously (22) and was explored further in this work by combining traditional measurements in IR research with 1 H-NMR spectroscopy-based metabonomics. The study design involved 14 claudicants and three healthy volunteers, who were subjected to a walking test before and after the intake of vitamins and after a washout period.…”
Section: Introductionmentioning
confidence: 94%
“…In CAD, the evidence points towards an increased oxidative stress associated with acute exercise; however, this effect may be dependent on induced ischaemia as detected hy a positive exercise treadmill test [42], The results from studies of exercised claudicants are variable. Khaira et al [43] showed a decrease in antioxidant concentration, although aspirin use was not apparent. Contrary to this, Lewis et al [44] identified elevated total antioxidant capacity in aspirin-treated claudicants after exercise.…”
Section: Discussionmentioning
confidence: 97%